Effects of Pulse Current Mode on Plasma Electrolytic Oxidation of 7075 Al in KMnO4 Containing Solution. Issue 12 (19th September 2017) - Aliramezani, Reihane; Raeissi, Keyvan; Santamaria, Monica; Hakimizad, Amin
Abstract : Plasma electrolytic oxidation of 7075 Al alloy was performed in alkaline silicate electrolyte containing KMnO4 as an additive using unipolar (U) and bipolar pulsed current modes (B1 and B2). The coating grown using the bipolar current with longer cathodic pulse time (B2) revealed a more dense foam-like surface morphology with fewer volcano areas providing higher thickness, which is mainly raised by reduction in discharge intensity. Also, a lower concentration of electrolyte elements (Si and Mn) was incorporated into the coating providing a brighter appearance. EIS results showed very high inner layer resistances for the coatings indicating this layer controls the overall corrosion performance of the coatings. In this way, the highest inner layer resistance along with very low value of constant phase element was achieved for the coating produced by B2, which is an indication for its lower porosity and higher thickness. Also, the more noble corrosion potential and lower passive current density observed for this coating in potentiodynamic polarization test confirms its stronger barrier effect against the chloride ingression where its corroded surface after long-term EIS test showed no significant damage. The lower penetration depth and subsequently the higher hardness values were achieved for the coatings produced by B2.